2008
DOI: 10.1200/jco.2008.16.2339
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy for Poor-Prognosis Anal Canal Carcinoma: A Phase II Study of the Cancer and Leukemia Group B (CALGB 9281)

Abstract: A combined-modality approach that includes induction treatment with FU and cisplatin followed by combined-modality therapy with FU, mitomycin C, and concurrent radiation results in long-term disease control in the majority of patients with poor-prognosis anal canal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…The authors showed that for locally advanced tumors, patients treated with neoadjuvant platinum based chemotherapy had significantly better complete response rates and overall survival rates in comparison with patients who did not. Recently, a phase II study of the cancer and Leukemia Group B (CALGB 9281) confirmed those data for locally advanced anal carcinomas [35]. This could potentially explain that colostomy free survival rates observed here favorably compare with the rates reported in the literature for such locally advanced tumors.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The authors showed that for locally advanced tumors, patients treated with neoadjuvant platinum based chemotherapy had significantly better complete response rates and overall survival rates in comparison with patients who did not. Recently, a phase II study of the cancer and Leukemia Group B (CALGB 9281) confirmed those data for locally advanced anal carcinomas [35]. This could potentially explain that colostomy free survival rates observed here favorably compare with the rates reported in the literature for such locally advanced tumors.…”
Section: Discussionsupporting
confidence: 78%
“…Another way to intensify treatment is limitation of treatment breaks duration: feasibility has been studied in some phase II studies, with different schedules [19,20,35,[40][41][42]. Phase III studies could objectively evaluate impact of treatment break reduction on local control, colostomy-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, because it has been shown to have activity in numerous other squamous cell cancers, its use in anal carcinoma is being evaluated. The Cancer and Leukemia Group B (CALGB) evaluated the regimen of induction chemotherapy with 5-FU (1,000 mg/m 2 continuous infusion days 1-4 and 29 -32) and cisplatin (100 mg/m 2 on days 1 and 29) followed by chemoradiation with 5-FU and mitomycin for patients with locally advanced anal cancer [27]. An initial report of 45 patients treated with this regimen showed a 50% 48-month colostomy-and disease-free survival rate.…”
Section: Combination Chemoradiationmentioning
confidence: 99%
“…This regimen was scheduled as a planned preoperative therapy. However, it soon became doubtful whether radical surgery was necessary, because the majority of resected specimens were completely free of tumor on pathologic examination.Since then, several series and prospective trials have demonstrated the feasibility and efficacy of this approach, however, the most appropriate RT dose, fractionation, techniques, and the most effective chemotherapy regimen (agents, number of neoadjuvant, concomitant, adjuvant cycles) remain to be established [2,5,8,13,19,21,27,29]. This review focuses on clinical trials and new developments in combining RT with induction, concurrent and maintenance chemotherapy and targeted agents.…”
mentioning
confidence: 99%